Survival psychology in Kevin Powers’ The Yellow Birds - M Alosman, M Ikbal; Raihanah M.M., (Penerbit Universiti Kebangsaan Malaysia, 2020)
After experiencing the American war in Iraq as a machine gunner in the U.S. Army, Kevin Powers deliberates on war and the risks surrounding the lives of all those involved in his debut novel, The Yellow Birds. This paper aims to uncover the survival psychology that underlies the behaviour of the two main characters in the novel, Private John Bartle and Private Daniel Murphy as well as other minor characters. Survival psychology expounds unpredictable and threatening situations where people’s lives are at stake. They either choose to fight, flight or freeze in reaction to these horrible experiences, that is, they either take action, surrender or eventually die. In the context of war, soldiers frequently face such deadly situations. The reactions of the characters to the circumstances of war and their success and/or failure to cope with its dangers are indicative of their survival mechanism. The novel is examined according to the three major periods of impact in survival psychology, specifically, pre-impact, impact and post-impact periods. Bartle overcomes the psychological consequences of his war experience years after leaving the army, but Murphy loses his faculties in the chasms of war and consequently dies. The psychological survival of those who overcome these risks physically is not guaranteed. Such terrifying experiences of death may make these people vulnerable and exposed to psychological repercussions such as psychosis.